2016
DOI: 10.1111/papr.12514
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Pain Measurements Using Computerized Cuff Algometry: A DoloCuff Reliability and Agreement Study

Abstract: Inter-rater reliability was excellent for PT, PTol, and TSI. Similarly, the intrarater reliability for PT and PTol was excellent, while borderline excellent/good for TSI. Therefore, the DoloCuff can be used to obtain reliable measures of pressure pain parameters in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Both the current and previous studies indicate that estimation of PPT is reliable regardless of the evaluated body region. In contrast, only a few studies have evaluated the reliability of cuff-PPTol in the short term, showing moderate to excellent reliability (0.74 to 0.96) [36,37]. This study reports similar ICC confidence intervals for cuff-PPTol-7, although the previous studies established a pain tolerance threshold with a computerized cuff at NRS 10 out of 10.…”
Section: Short-term Reliabilitysupporting
confidence: 44%
“…Both the current and previous studies indicate that estimation of PPT is reliable regardless of the evaluated body region. In contrast, only a few studies have evaluated the reliability of cuff-PPTol in the short term, showing moderate to excellent reliability (0.74 to 0.96) [36,37]. This study reports similar ICC confidence intervals for cuff-PPTol-7, although the previous studies established a pain tolerance threshold with a computerized cuff at NRS 10 out of 10.…”
Section: Short-term Reliabilitysupporting
confidence: 44%
“…In fact, we examined seven clinically-relevant inter-evaluator reliability studies that have been published since 2015 and found that for 4 of the 7 studies, it was unclear how benchmarks of reliability were determined (i.e., what constituted a good versus bad score) [ 18 – 21 ]. The three remaining studies each used a different source for inter-evaluator reliability interpretation guidelines, and thus used slightly different grading scales [ 22 24 ]. Additionally, reliability indices alone cannot tell us the error inherent to a group of evaluators attempting to measure a variable of interest.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are currently no studies that have formally assessed the test–retest reliability of other commonly employed experimental models of tonic muscle pain, such as the cold‐pressor test (Angius et al, 2015; Slysz & Burr, 2021) and ischaemic contractions (Jones et al, 2014; O'Leary et al, 2017). Conversely, the reliability of the pain response elicited from techniques such as cuff and point pressure algometry, which provide a measure of pain pressure threshold have been well established (for example, Chesterton et al, 2007; Graven‐Nielsen et al, 2015; Kvistgaard Olsen et al, 2017; Nussbaum & Downes, 1998). However, the ability of these methods to assess muscle pain specifically is confounded by the unavoidable stimulation of cutaneous nociceptors and low‐threshold non‐nociceptors alongside muscle nociceptors (Graven‐Nielsen & Arendt‐Nielsen, 2003).…”
Section: Discussionmentioning
confidence: 99%